Implementation of the Values ​​of Tauhid Education in Early Childhood at the Al Ihsan Tasikmalaya Kindergarten - Wildan Mahmudin; R. Marpu Muhyidin Ilyas; Nurwadjah Ahmad; Andewi Suhartini (al-Afkar, Journal For Islamic Studies, 2025)
The purpose of this study is to determine the implementation of monotheism education carried out in PAUD KB Al Ihsan Tasikamlaya as a form of instilling monotheism values ​​for early childhood. The approach used in this study is descriptive qualitative and the methods used to collect data in this study are observation, interview, and documentation methods. The results of this study are that in implementing the values ​​of monotheism education, it can be done by holding the following activities: Habituation of Dhuha Prayer together, Habituation of reading Asma` Al Husna before learning, Habituation of reciting shalawat, Memorizing selected letters and Commemorating Islamic holidays. Some obstacles faced in implementing the values ​​of monotheism education in PAUD KB Al Ihsan Tasikmalaya are two factors, namely Internal factors such as reduced student interest in learning, Different levels of student ability and Different levels of student learning diligence. External factors such as inadequate school facilities such as teaching aids that are not available at school so that teachers have a little difficulty in explaining learning materials.